Application of rubber band ligation as a treatment of internal hemorrhoids - Sari, Sevil Ozer; Yıldız, Coşkun (International Journal of Research in Medical Sciences, 2021)
Background: Aim was to more than three-quarters of the whole population will experience complaints of hemorrhoids at some point in their lifetime. The treatment of internal hemorrhoids includes medical, minimally invasive and surgical treatments. The aim of the study was to evaluate the data of patients who were applied with rubber band ligation (RBL) as a minimally invasive treatment method of internal hemorrhoids. Method: The study conducted in the gastroenterology department of Izmir Tepecik training and research hospital between December 2015 and December 2019. Demographic and laboratory data of the patients, the success and the complications rates of the procedure were evaluated retrospectively . Results: Evaluation was carried out in 45 consecutive patients, comprising 23 (51.1%) females and 22 (48.9%) males with a mean age of 54.62±7.82 years (range, 40-82 years). Procedural success rate was 91.1% and failure of treatment was seen in 8.9% of the patient. Recurrence rate of RBL procedure determined with control rectoscopy was found as 5.26% at 1 year follow-up. No major complications developed in any patient. Significant correlation was determined between the development of bleeding and the use of anticoagulants and anti-aggregants (p=0.003). No significant relationship was seen between the number of band ligation procedures and the development of complications (p=0.275). Conclusions: The application of RBL, which is widely used in the treatment of internal hemorrhoids, is a reliable and low-cost method that shortens the length of stay in hospital, which can be preferred in patients with high comorbidity risk for surgery.